KEPUASAN MAHASISWA PADA PELAYANAN DI LEMBAGA PENDIDIKAN FAKULTAS ILMU ADMINISTRASI UNIVERSITAS MADURA - Nur Azizah, Rina (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2018)
AbstractQuality academic services create qualified students as well, so student satisfaction becomes the benchmark of a college in providing the best service. The academic services of the curriculum, lectures, and finances will work well if supported by good management as well. Madura University is a private higher education institution located on the island of Madura, precisely located in Pamekasan District. The education program at the Faculty of Administrative Sciences is designed to meet the needs of human resources that meet competencies in public administration skills, as well as having a high level of community and national insight. The method used in this research is descriptive research method with a qualitative approach to a phenomenon conducted by an agency to its environment in an effort to produce the right service. The use of this method aims to determine the form of service provided by the Faculty of Administrative Sciences Madura University. Of the 5 indicators described, among others Tangibles (physical evidence), Reliability, Responsiveness, Assurance, Emphaty (empathy) explains that the quality of service at the Faculty of Administrative Sciences Madura University quite well, where the satisfaction of students Faculty of Administrative Sciences University of Madura explained that the problems experienced by students have been given prompt and appropriate solution by the staff of the Faculty of Administrative Sciences Madura University. Similarly, if students expect a certain level of service, then in fact students feel the service received in accordance with his expectations.Keywords: Service, Student